FAKTOR INDONESIA MENGIMPOR GARAM DARI AUSTRALIA TAHUN 2014-2017 - Bintang, Anggie Ayu; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This thesis illustrates Indonesia's interest in importing salt from Australiain 2014-2017. (The Indonesia-Australia Comprehensive Economic PartnershipAgreement) facilitates the two countries to carry out international cooperationincluding importing salt into concrete actions by the IA CEPA. The theoreticalframework that I use in this study is the Libralization perspective, the theory ofinternational cooperation and comparative advantage to compare the productionof two countries. Libralism proposed by David Ricardo. In the theory that I use, thegovernment must make appropriate policies and place salt as a strategic commodityin Indonesia. Because salt is used by everyone as a necessity, it cannot be replacedwith other commodities and commodities that play a role in economic mobilization.By maximizing the national salt industry center and with policies that can save saltfarmers and salt-using industries, Indonesia will achieve self-sufficiency.The aimof the IA-CEPA itself is to achieve a comprehensive, high-quality and mutuallybeneficial partnership, to facilitate the expansion of trade, investment andeconomic cooperation between close neighbors which will also contribute toeconomic growth in both countries and will strengthen institutional and humancapacity , supports market openness, facilitates innovation, encourages integrationtowards global values and enhances cooperation in the 'powerhouse' sectors.Keywords: Salt Commodities, Import, IA CEPA, Cooperation.